IMPLEMENTASI KEBIJAKAN PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) TINGKAT KELURAHAN PROVINSI DKI JAKARTA STUDI KASUS DI KELURAHAN KELAPA DUA DAN KELURAHAN DURI KEPA JAKARTA BARAT - Jilita Cahya Putri; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2017)
Implementation of the policy on the handling of Infrastructure and public facilities level of the village is a job that needs to be done immediately and not be delayed because it can result in a loss, the dangers and disturbing public interest/community in the area of the village and in order to speed up the functioning of the site/infrastructure and means of public assets or assets/damaged, dirty and/or disturb in accordance with the allocation. The purpose of this study is to describe and analyze how the implementation of a policy of Handling Infrastructure of public facilities (PPSU) DKI Jakarta Neighborhood Level as well as describing and analyzing the factors restricting factor and supporting the implementation of the policy on the handling of Infrastructure and public facilities (PPSU) level of the subdistricts of Jakarta. Research methods used by researchers is the qualitative research methods. Based on the results of research conducted by the researchers, it can be noted that the implementation of the policy on the handling of Infrastructure and public facilities (PPSU) DKI Jakarta Neighborhood Level pretty well. It can be seen starting from the stage of the preparation, implementation, up to the end of the implementation of the policy on the handling of Infrastructure and public facilities (PPSU) DKI Jakarta Neighborhood Level is in compliance with regulations of the Governor of the province of Jakarta Special Capital Region Number 169 by 2015 On the handling of Infrastructure and public facilities level of the village. But there is still a bit of a hindrance on workers ' employment behavior of PPSU, public support, and communication antarorganisasi and implementing activities. To overcome these barriers so researchers recommend making written sanction, then develop a comfortable working environment and approach to the problematic PPPSU, last held a socializing, work meetings, and publishing of written rules of Smart City with each of the subdistricts of Jakarta.